The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.jbusres.2016.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Critical brand innovation factors (CBIF): Understanding innovation and market performance in the Chinese high-tech service industry

Abstract: Brand innovation sweeps aside established practices and disrupts the status quo, resulting in the transformation of markets. The present study develops and tests a model of critical brand innovation factors (CBIF) by examining key factors influencing firm-level brands' innovation and increased market performance. Adapting both organizational elements and market response characteristics, the model integrates four key variables in China's industrial service markets: innovation, internationalization, market orien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 77 publications
0
30
0
2
Order By: Relevance
“…The study demonstrated that when brands are more innovative, their performance increases -brand innovation plays a fully mediating role on the effects of market orientation and organizational learning to market performance, but has no mediating effect on internationalization and market performance. A lack of innovation reduces market performance even when internationalization, market orientation, and organizational learning are present [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study demonstrated that when brands are more innovative, their performance increases -brand innovation plays a fully mediating role on the effects of market orientation and organizational learning to market performance, but has no mediating effect on internationalization and market performance. A lack of innovation reduces market performance even when internationalization, market orientation, and organizational learning are present [11].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Services marketing researchers establish that innovation benefits firms in multiple ways and that innovating services to match customers' needs increases the attractiveness of the firms' offerings (Nguyen et al, 2016).…”
Section: Innovationmentioning
confidence: 99%
“…In accordance with Nguyen et al (2016) a superior market performance requires not only information on customers, but also, to proactively implement innovative activities such as organizational learning, orientation towards markets, and internationalization efforts.…”
Section: Market Performancementioning
confidence: 99%
See 2 more Smart Citations